2021
DOI: 10.1002/cjoc.202100272
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Removable Backbone Modification Strategy to Prevent Aspartimide Formation in the Synthesis of Asp Lactam Cyclic Peptides

Abstract: Main observation and conclusion The synthesis of an Asp lactam derivative of A‐183, a selective inhibitor of Factor 7a with good anticoagulant and antithrombotic activity, is described. Our synthesis depends on the use of a removable backbone modification (RBM) strategy to prevent aspartimide formation, which thwarted all attempts to synthesize this target using direct solid‐phase peptide synthesis. Validation of the RBM strategy in the synthesis of a second Asp lactam derivative was also accomplished. The RBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previously it has been shown that aspartimide formation occurs in the synthesis of lactam cyclic peptides via Fmoc-SPPS using Asp (OAllyl). 7 As shown in Fig. 3a, Arg(Pbf ) was coupled to Rink amide AM resin to obtain resin-bound 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it has been shown that aspartimide formation occurs in the synthesis of lactam cyclic peptides via Fmoc-SPPS using Asp (OAllyl). 7 As shown in Fig. 3a, Arg(Pbf ) was coupled to Rink amide AM resin to obtain resin-bound 6.…”
Section: Resultsmentioning
confidence: 99%
“…6 To avoid this side reaction, our group developed a removable backbone strategy to protect the amide nitrogen of the preceding Asp, thus avoiding the aspartimide formation and con-structing an Asp-base lactam cyclic peptide. 7 However, the implementation of this strategy requires tedious operations. Recently, a method has been developed to protect the β-carboxyl group using a C-C bond protecting group, cyanosulfurylide (CSY).…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide-rich proteins including the hormone insulin and the cytokine signaling molecule interleukin-2 (IL-2) play important roles in biomedical, structural, and pharmaceutical studies and are widely used, sometimes after labeling or derivatization. Recent advances in solid-phase peptide synthesis, peptide ligation, and protein folding strategies have improved access to a variety of disulfide-rich proteins and greatly expedited their biomedical research, but some proteins, such as the systemic iron homeostasis regulatory hormone hepcidin, remain difficult to synthesize due to their poor folding efficiency. , Others, such as the 26 kDa homodimer cytokine interleukin-5 (IL-5) responsible for eosinophil growth and differentiation, cannot be folded in vitro at all. , …”
Section: Introductionmentioning
confidence: 99%